2007
DOI: 10.1097/01.olq.0000260949.35304.22
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine Use and Risky Sexual Behaviors During Heterosexual Encounters

Abstract: Methamphetamine use during heterosexual encounters appears to increase sexual risk-taking, especially when both partners are using it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
4
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 24 publications
4
48
4
1
Order By: Relevance
“…Younger age and having multiple sexual partners were associated with methamphetamine/cocaine use in all three venue types in this sample of Mexican migrant men. This finding is similar to other studies of methamphetamine use among heterosexuals (CDC, 2006;Molitor et al, 1998;Zule et al, 2007). Higher acculturation has previously been shown to be associated with illicit drug use among Mexican immigrants (Vega et al, 1998), similar to the association with methamphetamine/ cocaine use found in our study.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Younger age and having multiple sexual partners were associated with methamphetamine/cocaine use in all three venue types in this sample of Mexican migrant men. This finding is similar to other studies of methamphetamine use among heterosexuals (CDC, 2006;Molitor et al, 1998;Zule et al, 2007). Higher acculturation has previously been shown to be associated with illicit drug use among Mexican immigrants (Vega et al, 1998), similar to the association with methamphetamine/ cocaine use found in our study.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, because this was a cross-sectional design, the directionality of the associations may vary in that some of the factors may precede, be concurrent with, or pursue methamphetamine/cocaine use. Notwithstanding, the literature indicates alcohol binging is common at the time of using methamphetamine and cocaine, and jointly, promote unprotected sex, a greater number of sexual partners, and ultimately, an increased likelihood of becoming infected with HIV and other STIs (Colfax et al, 2004;Semple, Zians, Grant, & Patterson, 2005;Zule et al, 2007). Another limitation is that the drug use questions did not address intensity of use in the past 12 months.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because it seemed that reducing MA use may be essential for risk reduction in many men we selected motivational interviewing (MI) as our intervention approach. MI is a client-centered counseling style that brings about behavior change by working with clients to explore and resolve ambivalence [31,32]. The five central principles of MI are (1) using reflective listening to express empathy, (2) using reflective listening and objective feedback to develop discrepancy between client goals and current problem behavior, (3) avoiding arguments by giving the client the responsibility for the decision to change, (4) avoiding resistance instead of confronting or opposing it, and (5) supporting self-efficacy and optimism for change [31].…”
Section: Step 3 Select Appropriate Theoretical Methods and Strategiesmentioning
confidence: 99%
“…As documented in studies of heterosexual users, many of whom are parents, the highly addictive, sexually stimulating, "binge and crash" nature of methamphetamine may result in children being exposed to a set of parental behaviors that include parents staying "high" and awake for days, having multiple sex partners, exhibiting erratic and bizarre behaviors, and experiencing extreme euphoria followed by painful withdrawal symptoms (e.g., depression, paranoia, irritability, aggression, delusions, or hallucinations; Centers for Disease Control and Prevention, 2006;Cheng et al, 2010;Semple et al, 2004Semple et al, , 2005aZule et al, 2007). The children of methamphetamine users also may experience a chaotic home life, with inadequate supervision, inconsistent parenting, chronic neglect, parental aggression, violence, and other safety risks (e.g., exposure to chemical and toxic fumes from home-based methamphetamine laboratories, to weapons, or to criminal activity; Amatetti and Young, 2006;McMahon, 2005).…”
mentioning
confidence: 99%